ASSESSMENT OF NUTRITIONAL STATUS AND FREQUENCY OF COMPLICATIONS ASSOCIATED TO FEEDING IN PATIENTS WITH SPASTIC QUADRIPLEGIC CEREBRAL PALSY - Kamilla Tavares de Sousa; Gabrielle Bemfica Ferreira; Amanda Torido Santos; Quintiliano Siqueira Schroden Nomelini; Luciana Oliveira de Almeida Minussi; Érica Rodrigues Mariano de Almeida Rezende; Isabella Lopes Nonato (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To correlate the nutritional status with variables associated to the type of diet and feeding route of children and adolescents with spastic quadriplegic cerebral palsy (CP). Methods: This cross-sectional study included 28 patients aged ≤13 years old who presented a diagnosis of spastic quadriplegic CP and were followed by the nutrition team of the Outpatient Clinic for Special Patients of Hospital de Clínicas de Uberlândia - Universidade Federal de Uberlândia (HC-UFU), between July/2016 and January/2017. Consent forms were signed by the legal guardians. The nutritional status was evaluated and data on dietary complications food route and type of diet were collected. For the description of data, average and median values were used. Correlation was tested with Spearman's index. Significance was set at p<0.05. Results: 75% of patients used alternative feeding routes (nasoenteral, catheter or gastrostomy), 57% were eutrophic. The most frequent complications were oropharyngeal dysphagia, reflux and intestinal constipation. No correlation was found between the occurrence of complications and the nutritional status. There was a positive correlation between the diet received and the patient's nutritional status (0.48; p=0.01), i.e. individuals with adequate caloric and macronutrients intake had a better nutritional status. Conclusions: The results reinforce the need for continued nutritional guidance for the children's parents/caregivers, as well as the choice of an adequate rout of feeding to each child by the multi-professional team, in order to contribute to improved nutritional status and adequate dietary intake.